Behavior of liver cirrhosis at the "Arnaldo Milian Castro" Hospital from July 2007 to March 2009 - María Herminia Fajardo González; Merlyn Arce Nuñez; Yosvany Medina Garrido; Lisset Esteva Carral; Marcos Félix Osorio Pagola (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2010)
Background: Liver cirrhosis is among the top ten death causes in the developed world and also in Cuba, so it is important to know its clinical and epidemiological characteristics in order to propose appropriate preventive measures. Objective: To describe the behavior of liver cirrhosis in the "Arnaldo Milian Castro" hospital from July 2007 to March 2009. Method: A descriptive and cross-sectional study in all patients with a liver cirrhosis diagnosis that were undergoing follow-up in the hepatology consultation or died from this cause. As part of the study the medical records were consulted and patients in consultation were interviewed. After applying inclusion and exclusion criteria there was a final sample of 120 cases: 59 patients are alive and 61 of them died. Results: Groups of people from 40-49 years old (32.5%), male sex (60.8%) and white skin (93.3%) were predominant. The most frequent death cause was alcoholism (40%) especially in men, followed by viral causes (24.16%).The most frequent complication was ascites (53.3%). The main cause of death was upper gastrointestinal bleeding from esophageal varices (52.45%), 44% of the cases presented Child-Pugh B and 46% died within the year after the diagnosis. Conclusion: cirrhosis has a high rate of incidence and prevalence mainly in the male sex due to the high consumption of alcohol and the viral infections that can be related. More comprehensive studies are needed to increase the amount of knowledge on this issue.